Fluorescence behavior of cyanine fluorophore Cy3 confined in anodic porous alumina: Advanced surface analysis - Larosa, Claudio; Ţălu, Ştefan (Colloids and surfaces. A, Physicochemical and engineering aspects, 2025)
In this study, an advanced analysis of the three-dimensional (3-D) surface microtexture of anodic porous alumina (APA) arrays was conducted to investigate their efficacy in confining cyanine fluorophore Cy3. The microstructural characterization of APA plays a pivotal role in enhancing the understanding of the material's surface properties, especially when applied to biological arrays and fluorescent dye confinement. To achieve this, Atomic Force Microscopy (AFM) was employed to obtain precise 3-D surface microtexture data. These measurements were complemented by stereometric analyses, adhering to ISO 25178‐2: 2012 standards, ensuring a robust quantitative and qualitative evaluation of the surface micromorphology. The analysis revealed a clear correlation between surface roughness parameters and micromorphological changes as a function of varied processing conditions. Notably, the increase in certain fabrication parameters led to significant alterations in the superficial texture, with observable changes in the fractal dimension of the surface structure. The APA arrays, fabricated using a specialized anodization technique followed by a tailored annealing procedure, exhibited extraordinarily large pore sizes, ranging from 1 to 2 μm, which are well-suited for accommodating the Cy3 dye molecules. These pore dimensions offer an enhanced capacity for dye confinement, providing a stable environment for the cyanine fluorophore while promoting optimal fluorescence behavior. [Display omitted]